Male frequency in Caenorhabditis elegans increases in response to chronic irradiation. (2nd September 2022) - Quevarec, Loïc; Réale, Denis; Dufourcq‐Sekatcheff, Elizabeth; Car, Clément; Armant, Olivier; Dubourg, Nicolas; Adam‐Guillermin, Christelle; Bonzom, Jean‐Marc
Abstract: Outcrossing can be advantageous in a changing environment because it promotes the purge of deleterious mutations and increases the genetic diversity within a population, which may improve population persistence and evolutionary potential. Some species may, therefore, switch their reproductive mode from inbreeding to outcrossing when under environmental stress. This switch may have consequences on the demographic dynamics and evolutionary trajectory of populations. For example, it may directly influence the sex ratio of a population. However, much remains to be discovered about the mechanisms and evolutionary implications of sex ratio changes in a population in response to environmental stress. Populations of the androdioecious nematode Caenorhabditis elegans, are composed of selfing hermaphrodites and rare males. Here, we investigate the changes in the sex ratio of C. elegans populations exposed to radioactive pollution for 60 days or around 20 generations. We experimentally exposed populations to three levels of ionizing radiation (i.e., 0, 1.4, and 50 mGy.h −1 ). We then performed reciprocal transplant experiments to evaluate genetic divergence between populations submitted to different treatments. Finally, we used a mathematical model to examine the evolutionary mechanisms that could be responsible for the change in sex ratio. Our results showed an increase in male frequency in irradiated populations, and this effect increased with the dose rate. The model showed that an increase in male fertilization success or a decrease in hermaphrodite self‐fertilization could explain this increase in the frequency of males. Moreover, males persisted in populations after transplant back into the control conditions. These results suggested selection favoring outcrossing under irradiation conditions. This study shows that ionizing radiation can sustainably alter the reproductive strategy of a population, likely impacting its long‐term evolutionary history. This study highlights the need to evaluate the impact of pollutants on the reproductive strategies of populations when assessing the ecological risks.